The lives and deaths of shelter animals - Guenther, Katja M (Stanford University Press, 2020)
Monster is an adult pit bull, muscular and grey, who is impounded in a large animal shelter in Los Angeles. Like many other dogs at the shelter, Monster is associated with marginalized humans and assumed to embody certain behaviors because of his breed. And like approximately one million shelter animals each year, Monster will be killed. The Lives and Deaths of Shelter Animals takes us inside one of the country's highest-intake animal shelters. Katja M. Guenther witnesses the dramatic variance in the narratives assigned different animals, including Monster, which dictate their chances for survival. She argues that these inequalities are powerfully linked to human ideas about race, class, gender, ability, and species. Guenther deftly explores internal hierarchies, breed discrimination, and importantly, instances of resistance and agency.